Fine-tuning the practical relevance of a quality framework for integrated nature-based interventions in healthcare facilities. A qualitative interview study - Sterckx, Ann; Delbaere, Ben; De Blust, Geert; Spacova, Irina; Samson, Roeland; Van den Broeck, Kris; Remmen, Roy; Keune, Hans (Frontiers in Public Health, 2024)
Introduction Integrated nature-based interventions in healthcare facilities are gaining importance as promising health and biodiversity promotion strategies. This type of interventions combines the restoration of biodiversity in the vicinity of the healthcare facility with guiding patients in that natural environment for health outcomes. However, quality appraisal of these interventions is still poorly developed. Based on a recent scoping review, the authors developed a preliminary quality framework in support of healthcare facilities designing, implementing and evaluating integrated nature-based interventions. This present study aims to fine-tune the practical relevance of the quality framework within the emerging practice. Methods A qualitative interview study was conducted in seven healthcare facilities in Belgium. Using a combination of snowball and purposive sampling, 22 professionals, involved in the integrated nature-based intervention in their facility, participated in the study. The semi-structured interviews were transcribed and imported into NVivo. A deductive and inductive thematic analysis was used to explore the practical relevance of the quality framework. A stakeholders’ assembly review and a member checking of the findings were also part of the study. Findings Twenty-two interviews with nature management coordinators, healthcare professionals, and healthcare managers were conducted by three principal investigators in seven healthcare facilities implementing integrated nature-based interventions. The contextualization and complexity of integrated nature-based interventions in the participating healthcare facilities demonstrated the need for an evidence-based quality framework describing nature-based interventions. The study led to nine quality criteria, confirming the eight quality criteria derived from a previous scoping review, and the identification of a new quality criterion ‘Capacity building, leverage and continuity’. These quality criteria have been refined. Finally, a proposal for a quality framework was developed and operationalized in a checklist. Deployment of the quality framework should be embedded in a continuous cyclical, adaptive process of monitoring and adjusting based on evaluations at each phase of an integrated nature-based intervention. Discussion Bridging the domains of healthcare and nature management in the context of an integrated nature-based intervention in a healthcare facility requires a transdisciplinary approach. Scientific frameworks such as “complex interventions,” Planetary Health and One Health can support the co-design, implementation and evaluation of integrated nature-based interventions within a cyclical, adaptive process. In addition, the importance of the quality of the interactions with nature could gain from more sophisticated attention. Finally, the implications for healthcare facilities, policymakers and education are discussed, as well as the strengths and limitations of the study.